A Cogenerative Dialogues among Pre-service STEM Teachers on Nurturing a Culturally Responsive Learning Environment for Effective STEM Classrooms and Reflexive Practices on Thai Sociocultural Issues Classroom - Khwaengmek, Vipavadee; Wong, Yau Yan (วารสารนวัตกรรมการศึกษาและการวิจัย, 2024)
In this study, we investigated five pre-service STEM teachers’ cogenerative dialogues during the STEM teaching method course. A cogen was conducted to understand the challenges faced by participants when they are learning how to teach STEM in K-12 schools. During the course, we intend to introduce cogen as a pedagogical tool to pre-service STEM teachers to cultivate a democratic, equitable, and student-centered classroom. We adopted a hermeneutic phenomenological approach to describe and interpret participants’ lived experiences as a learner. We audiotaped and transcribed our interviews and cogen with participants. Data analysis through qualitative content analysis. Several themes emerged from the vignettes, including traditional teacher identity in Thailand, students’ fear of expressing themselves, and STEM education as an opportunity for cultural change. We can see that certain aspects of the Thai sociocultural context create some challenges for STEM teaching and learning: In the Thai sociocultural context, the role of the teacher is often dominant in the classroom setting. This culture’s effect on teaching and learning STEM. From the findings, STEM teachers in Thailand need to shift their teaching style to a student-centered approach. By nurturing a democratic classroom culture and promoting autonomous thinking, adding reflective thinking, and providing students with an opportunity to share their ideas. Fostering a democratic culture in STEM classrooms through regular co-generative dialogues allows students and teachers to get effective STEM classrooms.